APLIKASI ARSIP SURAT MASUK DAN SURAT KELUAR PADA DINAS KOPERASI DAN UMKM PROVINSI JAMBI BERBASIS WEB - Louis, Ahmad; -, Afrizal; Damayanti, Rezky (FORTECH (Journal of Information Technology), 2024)
Mail management in an organization plays an important role in the administrative process. In this case, the correspondence management system is one of the influencing factors in the management of letters at the Dinas Koperasi dan UMKM Provinsi Jambi. So it is hoped that the process of managing letters, both incoming and outgoing letters, can be carried out more, better, faster and easier. With the incoming and outgoing letters application, it can reduce the use of quite a long time in archiving letters and disposition, reduce the use of paper, reduces the possibility of errors in recording, speeds up the process of searching for letters, makes it easier to control the disposition of letters, and is easy to use. The design of this application also makes it easier to communicate data between departments and create reports that are always up to date and can be seen based on monthly and annual reports. Design This incoming and outgoing mail application was created using tools such as PHPMyAdmin, MySQL as the database and Wamp as the offline server. The results of this research are the design of the application for incoming and outgoing letters at the Dinas Koperasi dan UMKM Provinsi Jambi, and it can be concluded that the design of this application provides a lot of convenience in the process of managing letters. This research was conducted to create an archiving application, which can manage incoming and outgoing mail effectively according to the flow determined by the Dinas Koperasi dan UMKM Provinsi Jambi. Filing of letters is carried out electronically, namely storing softcopy documents, and is equipped with reports of incoming and outgoing letters. The research methods used to solve various problems that occur are literature, observation, interviews, data and system analysis, system design, program creation, program testing, program implementation. What results from this research is to produce an application that can manage incoming and outgoing mail according to the specified flow, and can solve current problems